Application of the Make A Match Cooperative Learning Model in Memorizing Short Surahs - Ishak, Siti Hindun (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to find out how to apply the make a match cooperative learning model in memorizing short letters at the Madrasah Ibtidaiyah al-Muhajirin, Bitung City. And examine and reveal the supporting and inhibiting factors in implementing the make a match type cooperative learning model in memorizing short letters at the al-muhajirin madrasah al-muhajirin Bitung City. Methodology: This research uses a descriptive qualitative approach with a focus on planning and implementing learning and involving class III students at Madrasah Ibtidaiyah Al-Muhajirin in memorizing short letters. Data collection methods involve observation, interviews, and documentation. Data analysis includes reduction, presentation and drawing conclusions. The indicator of the success of this research is students' mastery of the material according to the stated objectives. Main Findings: The main finding of this research is that the application of the make a match cooperative learning model is able to improve student learning outcomes in memorizing short letters at the Madrasah Ibtidaiyah al-Muhajirin, Bitung City. Through the use of question and answer cards in learning sessions, students are more involved and active in understanding the material. Student interaction in groups also encourages collaboration and helps each other in mastering learning content. Novelty/Originality of this study: The novelty of this research lies in the application of the make a match type cooperative learning model in the context of learning to memorize short letters in the Al-Quran at madrasah ibtidaiyah. This approach can provide a new alternative in improving the quality of learning and student learning outcomes in the field of religion, and can be adopted by similar educational institutions to overcome similar obstacles in learning.